Fairness concepts and the intrahousehold allocation of resources. - Farmer, Amy; Tiefenthaler, Jill (Journal of Development Economics, 1995)
The effects of parents' differing notions of fairness on intrahousehold allocation of resources are examined, and six alternative fairness concepts that are used in such situations are described. It is revealed that the household food allocations and the resulting health outcomes are different across each of the fairness concepts and that different children will benefit from different fairness concepts. The implications of these findings for empirical studies of intrahousehold distribution and policy interventions are considered.